Pengaruh Ekstrak Buah Naga Merah (Hylocereus polyrhizus) terhadap Kadar HDL Tikus Wistar Model Sindrom Metabolik: Hasil Penelitian - Valensia Putri Melliana; Jarot Subandono; Danus Hermawan; R. Prihandjojo Andri Putranto; Sarsono (PT Kalbe Farma Tbk., 2024)
Introduction: Metabolic syndrome is characterized by hypertension, central obesity, insulin resistance, and dyslipidemia. Hylocereus polyrhizus is known for its potential in treating metabolic syndrome. Method: Laboratory experimental study with pretest-posttest control group design. Thirty rats were divided into 5 groups: K1 and K2 as negative and positive control, K3, K4, and K5 as groups receiving red dragon fruit extract at doses of 60, 120, and 180 mg/200 gBW. Data were analyzed using one-way ANOVA, Tukey HSD test, paired T-test, and Pearson correlation. Results: The highest HDL levels were observed in K5, while the lowest was in K1. Pearson correlation revealed a strong relationship between the dose of Hylocereus polyrhizus and HDL levels. Conclusion: Hylocereus polyrhizus extract could significantly increase HDL level. In this study, the optimal dose was 180 mg/200 gBW.